Cognitive Load and Its Relationship to Sixth-Grade Female Students' Achievement in Science (Journal of the College of Basic Education, 2025)
The research aims to know:Identifying the level of cognitive load that sixth-grade science students suffer from while studying the Arabic languageThe current research followed the descriptive correlational approach, and the sample was selected randomly from (3) schools in the Al-Suwaira Education Directorate. The sample of female students consisted of (308) female, The researcher applied the research tools (cognitive load scale) to the selected sample of sixth-grade science students in the first part of the academic year (2024/2025). The application took place on the day of Thursday corresponding to (2/1/2025). She also applied the achievement test on the day of Thursday corresponding to (2/1/2025). The researcher used the statistical methods appropriate to the research objectives. After applying the Arabic language among sixth grade science students.The relationship between the level of cognitive load and the achievement of sixth-grade science students appeared to be a strong inverse relationship